Clinical Characteristic and Prevalence of Invasive Candidiasis Patient in Cipto Mangunkusumo Hospital - Kalista, Kemal Fariz; Chen, Lie Khie; Wahyuningsih, Retno; Rumende, Cleopas Martin (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Incidence of invasive fungal infections (IFI) are reportedly increasing in many countries. Candida is the most common cause of IFI. This study was conducted to determine the prevalence, clinical characteristics, and etiologic pathogen in adult patients with invasive candidiasis (IC) at Cipto Mangunkusumo Hhospital. Methods. This was a cross sectional study with restropective data collection fromof septic patients that’ medical records hospitalized in January 2012 until June 2014. Subjects were selected based on EORTC/MSG 2008 diagnostic criteria for IC. Demographic data, clinical and supporting data, diagnosis, etiologic pathogens, antibiotics, antifungal, outcome, and length of stay were recorded. Results. The IC prevalence at Cipto Mangunkusumo hospital was 12,3% (91 patients from total of 738 sepsis patients). Subjects consisted of 35 proven, 31 probable, and 25 possible invasive candidiasis patients. Candidemia was the most common form of IC and C. albicans was the most common etiologic pathogen. Mean age were 47,9 years, dominated with medical, non-neutropenic, and septic shock patient. Most patients had malignancy with lung infection. The most common medical intervention was urinary catheter. Most patients were given 3rd generation cephalosporin and the most common antifungal used was fluconazole. Forty four percent of IC patients did not get systemic antifungal treatment. Mortality rate was 64.8% and median length of stay were 27 days. Conclusions. IC prevalence was 12,3%. Mortality due to IC was high and C. albicans was the most common etiologic pathogen.